Strengthening Reinforced Concrete Beams with Vertical Perforations by using Steel-Plate Tubing - Shneet, Masharaq A.; Izzet, Amer F. (Engineering, Technology & Applied Science Research, 2024)
This study aimed to experimentally compare the bending behavior of reinforced concrete beams in the midspan zone of the maximum bending region with and without vertically perforated openings. Five rectangular cross-section beams were produced for this purpose: one solid specimen, one with an opening without reinforcing steel, and the remaining three had openings reinforced with steel tubes of thickness 1, 1.5, and 2 mm. The square opening width was 40 mm. All specimens were tested under a symmetric four-point loading until failure. The test results showed that all specimens failed in bending. The presence of an opening negatively affects the ultimate load-bearing capacity and bending. However, the bending behavior of the reinforced concrete beams exhibited superior performance as the thickness of the steel tube increased. Additionally, the maximum load-bearing capacity increased with increasing tube thickness.